EVALUATION ANALYSIS OF DISTANCE LEARNING AT JUNIOR HIGH SCHOOLS IN SOUTH TAPANULI REGION - A Siregar; D S Fauzia; G Salwa (ISER (Indonesian Science Education Research), 2021)
The pandemic COVID-19 has had many impacts on various aspects of people's lives in the world. One of the effects of the Covid-19 pandemic is on education around the world which has led to the closure of large schools, madrassas, universities and Islamic boarding schools. The spread of the virus which has spread very widely, the Indonesian government has issued social distancing and physical distancing policies to prevent more widespread transmission of the virus. So that the assessment and evaluation of learning in social distancing and physical distancing conditions carried out at home can use the remote assessment method. The purpose of writing this article is to find out how teachers evaluate students on distance learning during the pandemic COVID-19. The method used in this research was descriptive method. Descriptive method is a method used to describe, describe the phenomena that occur. This study used a quantitative approach. The quantitative approach aims to reveal something as it is (objective). The results that can be obtained from this study are distance learning teachers are very difficult to understand their students because during distance learning / offline the teacher can only provide a little material to students and the limited time given to the teacher during distance learning so that students also experience difficulties in receiving the lessons described by the teacher